Industrial Plants Commissioning Procedures Using Digital Process-Oriented Architecture. Issue 10 (2022) - Nascimento, Daniel Luiz de Mattos; Roeder, Alessandra Brancher; Calvetti, Diego; Mustelier, Alejandro Menés; Gonzalez, Fernando Rodrigues; de Araújo, Flavio Ney Magno
Abstract: In the Brazilian Oil and Gas industry, deep-water exploration projects are carried out by several international companies and rely on extensive supply chains. There is a need to put into operation several industrial installations in this context. The commissioning of industrial plants is complex and demands high resources to obtain high-quality assurance and maximum reliability. Furthermore, the industrial plant commissioning works are predominantly carried out through paperwork forms. Given the relevance of these activities, it is vital to invest in improving and digitising on-site processes. What is also notable is the lack of research in commissioning, mainly administrative field procedures. In this context, an Oil and Gas Company and a Centre of Reference in Innovative Technologies started a Research Technological Development (RTD) project to digitise industrial plants' commissioning procedures. This paper presents the work done on process mapping, requirements identification, improvement development and systems architecture. The project aims to develop an interoperable system to implement the digital commissioning procedures. The on-site workforce can receive and record the execution of the activity's information on mobile devices. Finally, it highlights how process-oriented RTD is relevant to achieving better results and engaging people.